THE ROLE OF ACCOUNTING INFORMATION IN PLANNING AND DECISION MAKING IN FINANCIAL MANAGEMENT IN UMKM IN SINGARAJA CITY - Hanafi, Moh. Imam; Paradila, I Made Pradnyana; Devi, Sunitha; Masdiantini, Putu Riesty (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
Micro, Small, and Medium Enterprises (UMKM) have a strategic role in driving economic growth in Indonesia, including in Singaraja City. However, UMKM financial management still faces various challenges, especially related to low accounting literacy and minimal use of accurate and relevant accounting information. This study aims to examine the role of accounting information in supporting financial planning and decision-making in UMKM in Singaraja City, and to identify factors that influence its implementation. Using a qualitative approach through surveys and interviews with UMKM actors, it was found that accounting information plays an important role in improving operational efficiency, financial planning, and data-based business decision-making. This study also compares the implementation of three digital accounting systems, namely BukuWarung, ESB POS, and SAAS, which show similarities in supporting automatic financial recording, ease of use, and reduction of human error, as well as differences in features, focus of use, and system complexity. The results of this study provide theoretical contributions to the development of MSME accounting literature as well as practical contributions in the form of recommendations for strengthening accounting literacy and developing training based on local needs.